Effects of player characteristics and periodization strategies on external and internal loads, wellness, and recovery in collegiate male basketball players - Zhang, S.; Li, M.; Xing, W.; Zheng, W.; Zhai, Z. (The Journal of Strength and Conditioning Research, 2026)
This study investigated the effects of playing time, player role, player position, and training cycles-both microcycles (the six days leading up to a match) and mesocycles (the four weeks preceding competition)—on PlayerLoad (PL), rating of perceived exertion (RPE),well-being (WB), and total quality recovery (TQR) in highly trained collegiate male basketball players. A total of 18 highly trained collegiate male basketball players were monitored across a continuous 2-month, resulting in a total of 804 training session observations. External load was quantified as PL using wearable tracking devices, while internal load was assessed through RPE. Well-being and TQR were measured using digital self-report questionnaires. The key findings showed that high-minute players (>26 minutes) exhibited significantly higher PL (p < 0.05, effect sizes [ES] = 0.34) and RPE (p < 0.05, ES = 0.33) compared with low-minute players (<26 minutes). Positional differences were also reported, with centers reporting significantly lower RPE than forwards (p < 0.05, ES = -0.67) and higher WB than guards (p < 0.05, ES = -0.88). In the microcycle analysis, the highest PL and RPE were observed 5 to 6 days before official matches. Mesocycle analysis showed a significant increase in PL and RPE during week 2, accompanied by a concurrent decrease in TQR. These results demonstrate that playing time, player role, player position, and training cycles significantly influence PL, RPE, WB, and TQR, underscoring the importance of individualized load management within microcycle and mesocycle structures to optimize performance and recovery in collegiate male basketball players.